Involving Local Students in International Short Course Program at Universitas Dhyana Pura - Suyasa, N L C P S; Dewi, P C (KnE Social Sciences, 2018)
This research aims to determine internal and external factors that affect local students of Universitas Dhyana Pura in participating the International Short Course Program called Intrapreneurship in Another Perspective. The program is uniquely designed as an Educational Tourism Program collaborates local with overseas students. The involvement of the local students just started since 2014 even though the program offered since 2008. The population in this research is local and overseas students who have participated in the IAP program with 30 sample respondents. Method of research is using SWOT analysis. It determines the internal factors that attract local students and also to promote the IAP program within the local students which automatically increase the English capability and ease cultural adaptation to overseas students. The external factors are increasing the time management of each individual students also giving better chance of exchange program and/or overseas training. The strategy to involve more local students through creating “buddy” program, open a language classes or language club to attract local students, advertise more of the program to all study programs at the University, and giving the expedience to local students in their regular classes especially on the classes that the credits are unable to be transferred. Keywords: educational tourism, external factor, internal factor, international program